Occurrence of extended-spectrum beta-lactamases in Salmonella enterica strains isolated from broilers and food of animal origin in Portugal - Clemente, Lurdes (2013)
Salmonella enterica is a zoonotic bacteria transmitted through the food chain and isolates harbouring extended-spectrum beta-lactamases (ESBLs) have emerged worldwide during the last decade, with the CTX-M group being particularly important. The aim of the present study was to determine the antimicrobial susceptibility of S. enterica strains isolated from broilers and food of animal origin and to characterize ESBLs producers. On the scope of the national antimicrobial resistance surveillance programme on Salmonella, a total of 283 strains isolated from broilers (n=100) and food of animal origin (n=183), were received at the National Laboratory of Veterinary Research in 2011. The minimum inhibitory concentration (MIC) of 11 antimicrobials (nalidixic acid, ciprofloxacin, ampicillin, cefotaxime, chloramphenicol, florfenicol, streptomycin, gentamicin, tetracycline, sulphamethoxazole and trimethoprim) for all isolates was determined by agar dilution method. Susceptibility towards cefoxitin was determined through disk diffusion method. Breakpoints were interpreted accordingly to EUCAST epidemiological cut-off values. ‘Non-wild type’ (‘NWT’) isolates for cefotaxime (MIC>0.5mg/L) and cefoxitin (<19mm) were screened for the presence of ESBL- (blaTEM, blaOXA, blaSHV, blaCTX) and PMA_-encoding genes, using PCR method. Sequencing was applied to fully identify beta-lactamases. Among broilers, we identified 62% of ‘NWT’ isolates for ciprofloxacin, 57% for nalidixic acid and 28% for sulphamethoxazole, whereas in isolates from food of animal origin, 71%, 63% and 56% were ‘NWT’ isolates for tetracycline, sulphamethoxazole and ampicillin, respectively. Among all, 5/283 (1.8%) strains presented ‘NWT’ MICs for cefotaxime and were multidrug resistant: 2 Salmonella Havana isolated from broilers and 3 Salmonella S. 4,[5],12:i:- isolated from food of animal origin (swine); these isolates had one blaCTX-M-type gene, and 2 from food of animal origin presented 1 blaTEM-type gene and 1 blaSHV-type gene, respectively; they were ‘wild type’ for cefoxitin and no PMAB-encoding gene was detected. To our knowledge, this is the first time in Portugal that ESBL-encoding genes, particularly from blaCTXM family, were detected in isolates of Salmonella Havana, a very common serotype isolated from our broiler population. It should also be emphasised that third generation cephalosporins are not allowed in the national poultry production, contrary to the large animal production, which may explain the detection of ESBL-encoding genes in our strains from swine origin. Horizontal gene transfer may be responsible for the coresistance of strains to non-beta-lactam antibiotics. This study shows that national animal health monitoring systems play an important role and should be improved in an international level.